Dukungan, Kepercayaan Keluarga dan Peran Suami terhadap Keputusan Pemilihan Penolong Persalinan pada Masyarakat Suku Madura - Abrori Abrori; Mardjan Mardjan; Rita Riana (Dian Nuswantoro Semarang, 2017)
Safe delivery is the delivery process performed by the skilled birth attendant who provides basic and emergency health care services to women and their newborns during pregnancy, childbirth and the postpartum period. During the delivery process, the women who gives birth requires emotional support, this support is important to minimize the intervention and to help have a succesful delivery. Culturally, Madurese are well known of their obedience to parents. This obedience is considered absolute and inviolable. This study aimed at finding out the correlation of family support and trust, husband’s role, and the decision in choosing the birth attendant among Madurese community This was quantitative study with cross sectional approach. The data were collected by conducting interview and questionnaire to 94 mothers, then analyzed by chi square test.The study indicated that the the mothers who had support from family was 74,5%, the family belief was 43,6, and support from husband was 64,9%. The motherprefered to choose the traditional birth attendant was 70,2%. The results of bivariate analysis revealed that there were significant correlation of family support (p value=0,001, PR=1,560), family belief (p value=0,009, PR=1,459), husband’s support (p value=0,000, PR=1,740) and the decision in choosing the birth attendant. From the findings, the health center of Kuala Mandor B is encouraged to routinely conduct maternal visit and early detection on the maternal health status.Keywords: birth attendant, family support, family belief, husband’s role